Rehabilitation Stages in Elderly Female Patients with Myocardial Infarction in the Post-Hospital Stage - o’g’li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2024)
Target: Define metrics to predict performance rehabilitation measures in patients with myocardial infarction (MI) at the stage of early inpatient rehabilitation. Methods: The study included 68 patients with MI who were transferred to the inpatient rehabilitation unit. Fulfilled clinical and laboratory studies, electrocardiography, echo-cardiography, treadmill and bicycle ergometric stress tests, test 6-minute walk (test 6MX), functional state (FS) was assessed with the definition of functional class (FC) and rehabilitation potential tsial (RP). A complex of therapeutic exercises (LG) No. 3 was prescribed, training on a bicycle ergometer and/or treadmill. Results: Evaluation of the effectiveness of rehabilitation in patients with MI was carried out as an increase in the distance of the 6MX test with improvement FC, and to improve the FS. In 46% of patients with MI at the beginning of the course of rehabilitation litation noted a drop in systolic blood pressure (SBP) on training loads, however, their correction allowed successfully complete the rehabilitation course. In the group of patients with improvement by one FC and more were lower in the proportion of people with low RP and the level of falling SBP by training loads compared with a group of patients without improvement reduction or with improvement within the same FC (p < 0.05). How more pronounced was the fall in SBP during HT (r = –0.59; p = 0.044) and cycling (r = -0.83; p = 0.042), the lower was the effectiveness rehabilitation according to the 6MX test. In the group of patients with improved FS by one FC or more, the level of fall in SBP during LT was lower, than in the group of patients without improvement or with improvement within the same FC (p < 0.05). Conclusion: The effectiveness of rehabilitation measures in patients with MI at the stage of early inpatient rehabilitation allows predict the following indicators: the level of falling SBP during cycling (total percentage of correct predictions - 100%); level fall in SBP during HT (less than 15 mm Hg and 15 mm Hg or more) (total percentage of correct predictions - 92.9%) (regression equations for predicting the effectiveness of rehabilitation measures acceptance in patients with MI). The effectiveness of rehabilitation measures in patients with myocardial infarction at the stationary stage Educational Institution "Bukhari State Medical Institute", Department of Cardiology and Internal Medicine 1. Educational Institution "Belarusian State Medical University", Department of Medical Rehabilitation and Physiotherapy, Minsk, Belarus 2.